Differential Privacy and Robust Statistics - Dwork, Cynthia (Proceedings of the 41th Annual ACM Symposium on Theory of Computing (STOC), 2009)
We show by means of several examples that robust statistical estimators present an excellent starting point for differentially private estimators. Our algorithms use a new paradigm for differentially private mechanisms, which we call Propose-Test-Release (PTR), and for which we give a formal definition and general composition theorems.